EU11 Regular Economic Report : Coping with External Headwinds - World Bank (Washington, DC, 2012)
This study claims that despite the challenging external environment, EU11 countries did well in 2011. First, economic growth strengthened to above 3 percent (from around 2 percent in 2010) and the region fully recovered its output losses from the global financial crisis. Second, fiscal measures delivered reduction of around 3 percent of GDP in the EU11 average fiscal deficit. Third, the financial sector remained resilient to renewed concerns about negative feedback loops between insecure sovereign debtors and fragile financial markets. However, the good performance conceals important shifts in economic sentiment that occurred during the year. While the growth momentum was still strong in the first half of 2011, it slowed toward the end of the year, as the region started to feel the impact of lingering concerns about European sovereign-debt markets, creeping oil prices, and the global slowdown. With the downward trend in economic activity, labor markets remained slack. Unemployment rates hovered around those recorded in the midst of the global financial crisis with sluggish employment growth. The paper points out that the European economic growth model has delivered unprecedented welfare to the continent over the last half century. In spite of its remarkable success, several aspects of the European economic growth model require reform to ensure that it is sustainable. Among the priorities for many European states today are providing incentives for labor mobility, making public finances more sustainable, and adapting social security systems to demographic developments, and harmonizing regulation across borders. This note zeroes in on the EU11 region to explore what is driving their prosperity and growth. The main messages related to the drivers of growth and prosperity in EU11 are as follows: 1) Convergence; 2) Trade and finance; 3) Enterprise and innovation; 4) Labor; and 4) Government.